Integrasi Fiqh dan Usul Fiqh dalam Kasus Batas Umur Pernikahan - Rohman, Holilur (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2015)
The universal and integral understanding of the Islamic law need an integrative effort between jurisprudence (fiqh) and legal maxim (usul fiqh) in an applicable form. Both have a close relationship in building the foundation and overall material of jurisprudence. Theoretically, legal maxim is an Islamic legal reasoning method that would later raise the jurisprudential material. Therefore, to understand and respond the social problem of Islamic law, the integration between jurisprudence and legal maxim is absolutely needed. The only partial understanding of Islamic law by simply studying its product as written in some classical books of fiqh will certainly make it uprooted from its own historical aspect. While implementing Islamic law merely rooted from its methodology cannot comprehensively catch the chain of Islamic legal thought. It is, therefore, a necessary to integrate between fiqh and usul fiqh to have an integral understanding of Islamic law. This study focuses to realize such effort with a specific discussion on the case of marriage age limit under the maslahah mursalah perspective. The result of the integration of fiqh and usul fiqh is that the minimum age of conducting marital contract based on Islamic law in Indonesia is sixteen years old for woman and nineteen years old for man. [Memahami hukum Islam secara universal integral memerlukan upaya integrasi antara fiqh dan ushul fiqh dalam bentuk aplikatif. Keduanya memiliki korelasi erat dalam membangun aturan formil dan materil hukum Islam. Secara teoritis, ushul fiqh merupakan metode penalaran hukum Islam yang kemudian akan melahirkan fiqh. Oleh karena itu, untuk memahami dan menanggapi masalah sosial hukum Islam, integrasi antara ushul fiqh dan fiqh mutlak diperlukan. Mempelajari hukum Islam dengan hanya bermodal pemahaman fiqh seperti yang ditulis dalam beberapa buku klasik fiqh tentu akan membuatnya tercerabut dari aspek historis sendiri. Sementara menerapkan hukum Islam hanya berakar dari metodologinya tidak dapat secara komprehensif menangkap rantai pemikiran hukum Islam. Oleh karena itu, diperlukan upaya mengintegrasikan antara fiqh dan ushul fiqh agar memiliki pemahaman integral dari hukum Islam. Penelitian ini berfokus untuk mewujudkan upaya tersebut dengan pembahasan khusus pada kasus batas usia perkawinan di bawah perspektif maslahah mursalah. Hasil integrasi fiqh dan ushul fiqh yang dilakukan menghasilakan kesimpulan bahwa usia minimal melakukan perkawinan berdasarkan hukum Islam di Indonesia adalah enam belas tahun untuk perempuan dan Sembilan belas tahun laki-laki.]